Terapi Aktivitas Kelompok Senam Otak pada Lansia dengan Kasus Demensia di Wisma Durian Panti Sosial Tresna Werdha Budi Mulia 2 Cengkareng Jakarta Barat - Siti Robeatul Adawiyah; Nur Ayu Fazri; Aulia Shafa Shalsabila; Mesi Maesaroh; Pujianti Listiani; Eni Hernawati; Deva Restu Sari; Ratih Pisesa Pebriyanti; Ayu Dyah Faradina; Siti Fatimah; Mila Mila; Cut Indah Rahmadani; Laraswati Putri Basuki; Siti Maharani; Meily Purnama Sari (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Dementia is a neurodegenerative syndrome that arises due to chronic progressive disorders accompanied by multiple higher function disorders such as calculation, learning capacity, language and decision making. The purpose of the activity: Refreshing the brain, Stimulating and maximizing brain function, Thinking more positively, Improving concentration, Balancing the body, Controlling stress well. Activities: doing brain exercises for dementia patients at Wisma Durian, the Budi Mulia 2 Cengkareng Social Institution.